Investigating Functional Variation across Academic Disciplines: A Multidimensional Analysis of Research Articles - Qadir, Uzma; Ahmad, Samina; Mastoor, Fareeha (Journal of Communication and Cultural Trends, 2023)
The current study aims to investigate the functional variation in academic writing across six major disciplines of sciences, namely biology, physics, and computer science and of social sciences, namely linguistics, sociology, and psychology research articles. Furthermore, the current study also compares the use of language in science and social sciences research articles (RAs). For this purpose, a corpus of 300 research articles from six sub-disciplines of science and social sciences journals was compiled to conduct the analysis. A Multidimensional Analysis Tagger using version 1.3.2 was selected to tag and evaluate the RAs corpus. The triangulation research method was deployed to analyze the data quantitatively and to interpret the results qualitatively. The findings indicate that there are functional differences in the language employed in academic disciplines, particularly in terms of being informational, non-narrative, and persuasive. Likewise, comparable outcomes were noticed in dimension 3. The findings indicate that there are functional differences in the language employed in academic disciplines, particularly in terms of being informational, non-narrative, and persuasive. Likewise, comparable outcomes were noticed in dimension 3. The results may be helpful for the researchers, students of different disciplines, and teachers to spot trends across various sub-disciplines.